Fulfillment of the Right to Health Through Screening for Reproductive Tract Infection Diseases (Prevention of Transmission from Mother to Child at the Pati District Health Center) - Rachmawati, Intan; Dewi, Yustina Trihoni Nalesti; Hartanto, Hartanto (Soepra Jurnal Hukum Kesehatan, 2023)
Health services for pregnant and maternity women should pay attention to human rights. this study aims to find out the human rights rules that guarantee health rights of pregnant women and children, the regulations for screening reproductive tract infections (RTI) in pregnant women at pati regency’s health centers, and the suitability of rti screening implementation with human rights regulations.This Research Uses Juridical-Sociological Approach. The Specification Of Research Is Explanative. The independent variables in this study were all laws and regulations related to health rights, while the dependent variable was implementation of RTI screening for pregnant women at the pati regency’s health center. Data in this study came from primary data in the form of interviews and secondary data in the form of laws and regulations. The data was analyzed by qualitative approach to primary and secondary data.The human rights regulations that guarantee health rights of pregnant women and children are in article 28 paragraph (1) of the 1945 constitution, article 9 of law number 39 of 1999, and article 10 of law number 36 of 2009. Implementation of RTI screening for pregnant women in pati regency’s health center is regulated in central java provincial regulation number 5 of 2009 and pati regency regional regulation number 129 of 2018. Suitability of rti screening implementation with human rights refers to article 19 of law number 36 of 2009. Implementation of screening for pregnant women is guaranteed in article 13 paragraph 7 letter h. Regulation of the minister of health number 21 of 2021.